2023
DOI: 10.1038/s41598-023-30660-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of tumble finishing as a final post-treatment for fatigue enhancement of notched laser powder bed fusion AlSi10Mg

Abstract: A hybrid post-treatment combining tumble finishing as a final step after shot peening and heat treatment was developed to alleviate the adverse effects of internal and surface defects on the fatigue performance of laser powder bed fusion AlSi10Mg samples. The effects of each post-treatment were investigated individually and synergistically on microstructure, surface morphology and roughness, hardness, residual stresses, porosity, and rotating bending fatigue behavior of V-notched AlSi10Mg samples. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In recent studies, it has been observed that the formation of surface nanocrystallization, superior microstructure and mechanical performance with the effect of deformation has resulted in a positive change in corrosion. In this study, the formation of surface nanocrystallization with increase in deformation and the effective reduction of surface roughness, especially in additive manufacturing samples, have positively affected the corrosion performance [25,[44][45][46][47][48][49].…”
Section: Corrosion Resistancementioning
confidence: 86%
“…In recent studies, it has been observed that the formation of surface nanocrystallization, superior microstructure and mechanical performance with the effect of deformation has resulted in a positive change in corrosion. In this study, the formation of surface nanocrystallization with increase in deformation and the effective reduction of surface roughness, especially in additive manufacturing samples, have positively affected the corrosion performance [25,[44][45][46][47][48][49].…”
Section: Corrosion Resistancementioning
confidence: 86%
“…For instance, Wu et al [24] employed SP as a pretreatment method in conjunction with carburization treatment to improve the fatigue performance of heavy-duty gears. Maleki et al [25] utilized SP as a post-treatment method in a combined process to mitigate the negative effects of defects on the fatigue performance of AlSi10Mg samples. Croccolo et al [26] implemented SP as a post-processing method, demonstrating its capacity to boost the fatigue strength of 15-5 PH stainless steel, approaching levels achieved by forging processes.…”
Section: Introductionmentioning
confidence: 99%